Promising precision medicine: how patients, clinicians and caregivers work to realize the potential of genomics-informed cancer care. Issue 3 (3rd July 2022) - Ackerman, Sara L.
Abstract : This paper examines the emerging field of molecular oncology, in which targeted treatments are sought for patients who have exhausted standard cancer therapies. Drawing on an ethnographic study at a U.S. academic medical center, and building on recent theoretical work examining potentiality as a site where expectations, meaning and value are produced, I describe efforts to translate genetic information into extended life for patients. Clinicians, patients and families performed various types of largely-unrecognized labor that invested precision medicine with potential even when life-prolonging therapies remained elusive. Their future-making work was enabled and constrained by the structural conditions of U.S. health care. In this context potentiality was a generative force that was harnessed to the interests and inequities of a market-driven health system, raising important questions about who is able to participate in, contribute to, and benefit from emerging innovations and narratives of hope.